Stacked Modalities' Thromboprophylactic Therapy for Patients Undergoing Total Knee Replacement Surgery - Jiang, Limin; Zhang, Shudong; Zhao, Yuchi (The Journal of Knee Surgery, 2017)
Thromboprophylaxis is a controversial and challenging topic in joint replacement surgery. Mechanical prophylaxis in combination with the use of anticoagulants have been shown to have greater efficacy than single modalities. But the early use of anticoagulants has the potential to increases the risk of postoperative bleeding. The purpose of this study was to evaluate the thromboprophylactic effects of sequential combined method using early-mechanical compression with delayed rivaroxaban in total knee arthroplasty. A retrospective cohort study, including 369 patients receiving simultaneous combined mechanical and pharmacological thromboprophylactic modality and 385 patients receiving sequential combined modality with early-mechanical compression treatment followed by rivaroxaban 2 days later after primary total knee arthroplasty surgery was conducted. The incidence rates of proximal and distal deep vein thrombosis (DVT) on the 2nd day and the 5th week and the volume of wound drainage were compared postoperatively. On the 2nd postoperative day, the incidence rates of proximal and distal DVT in the sequential group (1.56, 4.16%) had no significant difference compared with those (1.08, 3.25%) in the simultaneous group (p = 0.569, 0.507, respectively). No difference was found in the incidence rate of proximal and distal DVT on the 5th week between groups. No pulmonary embolism occurred. The mean volume of wound drainage in the sequential group was 343 mL which was 98 mL lesser than in the simultaneous group (p < 0.001). The sequential combined method as called “stacked modalities” thromboprophylactic therapy following total knee arthroplasty was safe and effective. The use of the mechanical compression method alone during the early-postoperative 48 hours, then followed by rivaroxaban then until the 5th week had the same antithrombotic effects and reduced the postoperative wound drainage volume as compared with simultaneous combined modalities.
Keywords: total knee arthroplasty; deep vein thrombosis; intermittent pneumatic compression